The Role Of Motivati On As Intervening In The Relationship Between Communication To Employee Performance - Hery Verianto The; Nova Arestia (Jurnal Manajerial, 2022)
Backround – The existence of human resources will determine the success of the organization. In every company activity, human resources play a major role. Purpose – This research aims at examining and analyzing the impact of communication on employee performance at Hotel My Home Pontianak with motivation as intervenning variables. Design/ Methodology/ Approach – Research method applied is causal approach survey in form of quantitative causal description. Census technic is used to collect the primary data, with repondents as many as 60 employees at Hotel My Home Pontianak. Finding – Secondary data was elicited from Website Hotel My Home Pontianak. Conclusion – The test results of the research shows that communication has positive and significant effect on motivation, motivation has positive and significant effect on employee performance, communication has positive and significant effect on employee performance, motivation mediates the effect of communication on employee performance, direct effect of communication on employee performance stronger than motivation mediates the effect of communication on employee performance. Research Implications - The application of intense and effective communication between management and employees will be able to increase motivation and have an impact on employee performance so that the sustainability of Hotel My Home Pontianak can be maintained. Limitations - Although this research contributes to the field of human resources, there are still limitations that require further research. First, the variables used are limited to communication, motivation and employee performance, even though there are many other variables that can affect employee performance, such as employee engagement, organizational commitment, job satisfaction and so on. Second, the number of samples used is still limited. Third, this research was only conducted on one hotel, so it needs to be done also on other hotels to get maximum results.